Edukasi Perundungan Dan Dampaknya Pada Konselor Remaja Panti Asuhan Al Fallah: Bullying Education and its Impact on Youth Counselors at Al Fallah Orphanage - Akbar, Resti Rahmadika; Anissa, Mutiara; Hariyani, Insil Pendri (Vivabio: Jurnal Pengabdian Multidisiplin, 2024)
Bullying, also known as bullying, is a physical, verbal, or psychological action against a weak group carried out by a superior person or group. Bullying can occur in schools, Islamic boarding schools, or orphanages. Bullying sometimes goes unnoticed, so awareness of all parties needs to be increased so that the impact of bullying on victims can be prevented. This service targets teenagers who live in the Al Falah orphanage and students at the Al Falah Islamic Boarding School. The service activities began with providing material regarding bullying and how to prevent it, then continued with discussions and sharing experiences regarding bullying. Next is a quiz to assess participants' understanding of bullying and its prevention. The quiz participants' knowledge of the material showed that 93% could answer seven questions correctly. It is estimated that schools, Islamic boarding schools, or institutions have anti-bullying and bullying prevention programs at school so that problems resulting from bullying will not be serious. Focusing on promotion and prevention will have a good impact on all parties.   ABSTRAK Perundungan atau dikenal juga dengan bullying merupakan tindakan baik fisik, verbal maupun psikis kepada kelompok yang lemah yang dilakukan oleh sesorang atau kelompok yang lebih unggul. Perundungan dapat terjadi di sekolah, pesantren ataupun panti asuhan. Perundungan kadang tidak disaadari terjadinya, sehingga perlu ditingkatkan kesadaran semua pihak agar dampak bullying  pada korban dapat dicegah. Pengabdian ini sasarannya pada remaja yang tinggal di panti asuhan Al Falah sekalaligus sebagai santri di Pesantren Al Falah. Kegiatan pengabdian dimulai dengan pemberian materi mengenai perundungan dan cara pencegahannya, kemudian dilanjutkan dengan diskusi serta berbagi pengalaman mengenai perundungan. Selanjutnya kuis untuk menilai pemahaman peserta menegnai perundungan dan pencegahannya. Hasil dari kuis pemahaman peserta terhadap materi 93% dapat menjawab benar 7 pertanyaan. Diharapkan sekolah, pesantren atau panti punya program anti perundungan dan pencegahan perundungan di sekolah, sehingga permasalahan akibat perundungan tidak akan berat. Fokus pada promotif dan pencegahan akan berdampak baik untuk semua pihak.